Zones with Potential for the Payment of Environmental Services in the Valle del Mezquital, Hidalgo - Aguilar-Sánchez, Genaro; González-Vizcarra, Reynol (Revista de Estudios Andaluces, 2019)
The arid regions in Mexico are excluded from the benefits of the Payment for Environmental Services (PES) scheme of the National Forestry Commission, due to the low forest cover they have. The objective of the work is to carry out an identification at the regional level of those potential payment zones for environmental services in the Mezquital Valley, Hidalgo State. The limitation of the arid zone is the main justification for generating proposals as alternatives to try to include these regions in the PSA. The identification of eligible or priority areas for the PSA was based on the methodologies of the Physiographic Survey, to delimit the environmental areas or units and, for the analysis of decision-making, the Multicriteria. Priority areas for payment for environmental services equivalent to 911 ha were identified, with high and very high risk characteristics of losing the ecosystem services provided by the conservation of biodiversity.